Rapid detection of Mycobacterium tuberculosis based on cyp141 via real-time fluorescence loop-mediated isothermal amplification (cyp141-RealAmp) - Zhu, Yinyin; Feng, Zi; Xu, Yinfang; Luo, Sha; Zhang, Ruixian; Shi, Xudong; Wu, Xuping; Zhang, Hongying (Frontiers in Cellular and Infection Microbiology, 2024)
Background The rapid detection of Mycobacterium tuberculosis (MTB) is essential for controlling tuberculosis. Methods We designed a portable thermocycler-based real-time fluorescence loop-mediated isothermal amplification assay (cyp141-RealAmp) using six oligonucleotide primers derived from cyp141 to detect MTB. A combined number of 213 sputum samples (169 obtained from clinically diagnosed cases of pulmonary TB and 44 from a control group without tuberculosis) underwent Acid-fast bacillus (AFB) smear, culture, Xpert MTB/RIF assays, and cyp141-RealAmp assay. Results By targeting MTB cyp141, thistechnique could detect as low as 10 copies/reaction within 30 min, and it was successfully rejected by other mycobacteria and other bacterial species tested. Of the 169 patients, there was no statistical difference between the detection rate of cyp141-RealAmp (92.90%, 95% CI: 89.03-96.07) and that of Xpert MTB/RIF (94.67%, 95% CI: 91.28-98.06) (P > 0.05), but both were statistically higher than that of culture (65.68%, 95% CI: 58.52-72.84) (P < 0.05) and AFB (57.40%, 95% CI: 49.94-64.86) (P < 0.05). Both cyp141-RealAmp and Xpert MTB/RIF had a specificity of 100%. Furthermore, a high concordance between cyp141-RealAmp and Xpert MTB/RIF was found (Kappa = 0.89). Conclusion The cyp141-RealAmp assay was shown to be effective, responsive, and accurate in this study. This method offers a prospective strategy for the speedy and precise detection of MTB.